PENGARUH IOS, SIZE, IKLAN SERTA CSR TERHADAP PROFITABILITAS - Anggi Reftiana (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research was to determine the influence of partial and simultaneous variables Investment Opportunity Set, Size, Advertising and Promotion as well as Corporate Social Responsibility on profitability study on banking companies listed on the Indonesia Stock Exchange 2016-2019 period. The type of research is assosiatif causal with quantitative method. The sample in this research was purposive sampling method with total 10 banks out of popolations of 45 banking companies with data collection in the form of documentation in the form of financial statements and sustainability report. Data analysis techniques used in this study was multiple linier regressions with panel data approach that usig the tool eviews 9.0. The t test result partially indicate that the Investment Opportunity Set variable has negative and significant influence on profitability, Size variable has negative and significant influence on profitability, Advertising and Promotion variable has positive and significant influence on profitability, and Corporate Social Responsibility have positive and not significantly influence on profitability. The F test result simultaneously indicate the effect of Investment Opportunity Set, Size, Advertising and Promotion as well as Corporate Social Responsibility significantly influence profitability